Experimental, DFT and Theoretical Corrosion Study for 4-(((4-ethyl-5-(thiophen-2-yl)-4H-1,2,4-triazole-3-yl)thio)methyl)-7,8-dimethyl-2H-chromen-2-one - Parlak, Akif Evren; Omar, Rebaz Anwar; Koparir, Pelin; Salih, Musher Ismael (Scientific Scholar Llc, 2022)
In this work, 4-(((4-ethyl-5-(thiophen-2-yl)-4H-1,2,4-triazole-3-yl)thio)methyl)-7,8-dime thyl-2H-chromen-2-one was synthesized by acetone-mediated condensation of 4-ethyle-5-(thio phen-2-yl)-4H-1,2,4-triazole-3-thiol and 4-(chloromethyl)-7,8-dimethyl-2H-chromen-2-one. The molecule results (3) were experimentally characterized using FT-IR, 1H-, and 13C NMR spectroscopy. Density Functional Theory (B3LYP/cc-pVDZ) was used to investigate the ideal molecule structure, vibrational frequencies, and 1H with 13C NMR (theoretically) chemical shifts. Theoretical and experimental spectroscopy results were compared and agreed with each other, which indicated the validity of the used developed molecular structure. The Dipole moment, hardness, softnes, electronegativity, electrophilicity index, nucleophilicity index, and chemical potential as electronic structural parameters linked to corrosion inhibition efficacy were investigated for the prepared compound. Furthermore, the fraction of transferred electrons was calculated to determine the interaction between the iron surface and organic molecules. The results indicated a favorable relationship between organic-based corrosion inhibitors and quantum chemical parameters processes. The corrosion inhibitors' behavior can be predicted without the need for experimental investigation.(c) 2022 The Authors. Published by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Anti -corrosion; DFT; FT-IR; NMR spectroscopy; Substituted 1; 2; 4-Triazole